Peningkatan kelincahan pada atlet remaja bolavoli menggunakan latihan ladder drill - A, Setiawan; Bujang, Bujang (Motion: Journal Research of Physical Education, 2022)
This research is motivated by the importance of agility in volleyball games, especially in overcoming opponents' attacks, especially covering space when blocking and smashing the ball and dumb play from opponents. The method used in this study was an experiment with one group pre-test post-test design. The population and sample in this study were 17 teenage athletes of the Dahlia volleyball club. The results of the research analysis showed that ladder drill training can increase agility in volleyball adolescent athletes, the magnitude of the increase in agility by 34.3%.